Pelaksanaan Keselamatan Dan Kesehatan Kerja (K3)Terhadap Upaya Zero Accident - Deli Cintya; Yulianti Keke; Alit Sodikin (Institut Transportasi dan Logistik Trisakti, 2021)
The purpose of this study was to determine how the effect of the implementation of occupational safety and health (K3) and behavioral awareness (K3) of the depok-antasari toll road service operational officers on zero accident efforts at PT Citra Waspphutowa. This research was conducted on 48 respondents using a quantitative descriptive approach. By using two independent variables, namely the implementation of occupational safety and health (K3), awareness of behavior (K3) and one dependent variable, namely zero accident efforts. This study aims to determine the effect of the implementation of occupational safety and health (K3) (X₁) and awareness of behavior (K3) (X₂) on efforts to zero accident (Y). The results of this study show simultaneously (F test) the variables of the implementation of occupational safety and health. (K3) and awareness of behavior (K3) together have a positive and significant effect on zero accident efforts with a contribution value of 67.3%. Partially (T test) awareness of behavior (K3) has a positive and significant effect on zero accident efforts.